Peningkatan Literasi Kesehatan Mental Remaja melalui Penyuluhan Interaktif di STIKes Maranatha Kupang - Delice Vebrida Pobas; Reashly Mokola; Christina Nayoan; Noorce Ch. Berek (Compromise Journal Community Proffesional Service Journal, 2025)
Mental health counseling is a vital strategy to enhance adolescents’ understanding of psychological well-being. This activity was carried out by postgraduate students from Nusa Cendana University at STIKes Maranatha Kupang, involving 10 participants. The method used was participatory counseling through seminars and group discussions. Evaluation was conducted using pre-test and post-test instruments to measure changes in knowledge, attitude, and behavior. The results showed an increase in knowledge scores from 62.3 to 84.7; attitude from 68.1 to 80.2; and behavior from 60.5 to 74.3. This program proved effective in improving mental health literacy among adolescents.